2021
DOI: 10.1097/gme.0000000000001900
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting surgical decision-making in carriers of BRCA1/2 pathogenic variants undergoing risk-reducing surgery at a dedicated hereditary ovarian cancer clinic

Abstract: Objective: Women with germline BRCA1/2 pathogenic variants have a significantly elevated lifetime risk of ovarian and fallopian tube cancer. Bilateral salpingo-oophorectomy (RRSO) is associated with a 90% reduction in the development of tubal and ovarian cancer. At our tertiary hospital, we have a dedicated clinic where women predisposed to hereditary ovarian/tubal cancer receive counseling on reproduction, risk reduction, surgical prophylaxis, and menopausal aftercare. The objective of this study was to evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Considering the minimal complications associated with hysterectomy at RRSO, this procedure can be a treatment alternative to avoid EC. A recent study from Canada reported that 8.9% of women chose to undergo concurrent hysterectomy for fear of developing EC 23 . As there is no confirmed method to detect EC at its early stages, prophylactic hysterectomy can be an option for women with BRCA1/2 PVs.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the minimal complications associated with hysterectomy at RRSO, this procedure can be a treatment alternative to avoid EC. A recent study from Canada reported that 8.9% of women chose to undergo concurrent hysterectomy for fear of developing EC 23 . As there is no confirmed method to detect EC at its early stages, prophylactic hysterectomy can be an option for women with BRCA1/2 PVs.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the minimal complications associated with hysterectomy at RRSO, this procedure can be a treatment alternative to avoid EC. A recent study from Canada reported that 8.9% of women chose to undergo concurrent hysterectomy for fear of developing EC [23]. As there is no con rmed method to detect EC at its early stages, prophylactic hysterectomy can be an option for women with BRCA1/2 PVs.…”
Section: Discussionmentioning
confidence: 99%